PENGEMBANGAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN BERBICARA DAN KEAKTIFAN BELAJAR DI KELAS VI MI ASSULTHONIYAH KOTA PROBOLINGGO - Alfat, Korik; Khosiah, Nur; Fadilah, Yulina (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Education has an important role in the process of developing students' potential, with a special emphasis on the role of mathematics, especially the subject matter of flat-sided spaces. Although efforts have been made to improve the quality of education, there are still problems, especially related to students' desire to learn mathematics. The importance of learning media that is interesting and easy to understand has become a major concern. In this case, the human body structure media, which is centered on the material of human body recognition which is one of the discussions of Biology lessons in grade VI SD / MI. This Research and Development study uses the ADDIE model. Validity by media experts and material experts is required during the development process. The results showed that this media, can bring changes to student learning outcomes so that they can experience an increase from before. The creation of human body structure media can be considered as a fun innovation. This media also has the potential to improve speaking skills and learning activeness and can be applied in the world of education.